2001
DOI: 10.1007/s11664-001-0119-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microstructural evolution and intermetallic layer growth on shear strength of ball-grid-array Sn-Cu solder joints

Abstract: The shear strength of ball-grid-array (BGA) solder joints on Cu bond pads was studied for Sn-Cu solder containing 0, 1.5, and 2.5 wt.% Cu, focusing on the effect of the microstructural changes of the bulk solder and the growth of intermetallic (IMC) layers during soldering at 270∞C and aging at 150∞C. The Cu additions in Sn solder enhanced both the IMC layer growth and the solder/IMC interface roughness during soldering but had insignificant effects during aging. Rapid Cu dissolution from the pad during reflow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 19 publications
(20 reference statements)
0
20
0
Order By: Relevance
“…The intermetallic compounds, which form between the SAC and copper base are similar to those found in the Sn-Pb/Cu connections. Also some studies are reported on intermetallic phases found in the Sn-Cu solder joints [3] and Sn-Ag [1,4,5]. Besides, various additions to the Sn-Ag alloy such as Ni, Cu, Al, Zn, Co, Sb, P and Au were studied in [6] and the interface layer is similar to that found in SnZn with additions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intermetallic compounds, which form between the SAC and copper base are similar to those found in the Sn-Pb/Cu connections. Also some studies are reported on intermetallic phases found in the Sn-Cu solder joints [3] and Sn-Ag [1,4,5]. Besides, various additions to the Sn-Ag alloy such as Ni, Cu, Al, Zn, Co, Sb, P and Au were studied in [6] and the interface layer is similar to that found in SnZn with additions.…”
Section: Introductionmentioning
confidence: 99%
“…The application of Sn-Pb alloys into copper-based connections causes the formation of the Cu 6 Sn 5 and Cu 3 Sn compounds. The increased growth of the intermetallic layers of CuSn decreases thermal endurance, tensile strength and brittle fracture of the solder joint.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] These works suggest that, upon contact, Cu and liquid Sn react to form two distinct IMCs [Cu 6 Sn 5 (g phase) and Cu 3 Sn (e phase)], which precipitate at different stages of the soldering reaction. Most research seems to suggest that, at the very early stages of the soldering reaction, the g phase precipitates first.…”
Section: Introductionmentioning
confidence: 99%
“…19 Earlier works have focused on experimental characterization of the late stages of growth and coalescence of g and e phases during lead-free soldering reactions between Sn and Cu. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] More recently, several groups have investigated the formation of the g phase at the early stages of soldering reactions. [20][21][22][23] These latter works have found that individual Cu 6 Sn 5 grains seem to appear at random positions along the (metastable) solid/liquid interface within a few milliseconds.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the solder/ substrate interactions and their microstructural evolution at the interface is important as it can provide insight into the nature of the interfacial evolution from a metallurgical point of view. [8][9][10][11][12][13] At the same time, accurate control of these reactions can have significant impact on the optimization of the soldering process. 14 Experimental investigations of intermetallic compound growth 6,7,13,[15][16][17][18] indicate that Cu 6 Sn 5 layer is formed as scallop-type grains in contact with liquid solder, while Cu 3 Sn is usually formed between the Cu substrate and the Cu 6 Sn 5 layer.…”
Section: Introductionmentioning
confidence: 99%